Pathological Q-Waves With Coronary Artery Spasm - Hirota, Yumi (JACC Case Rep, 2021)
This case highlights the diagnostic challenge associated with myocarditis, especially when accompanied by coronary spasm. Any coronary spasm with hemodynamic instability and/or an inexplicable widespread electrocardiogram should alert the clinician to the possibility of fulminant myocarditis and the necessity of endomyocardial biopsy for treatment decisions. (Level of Difficulty: Beginner.)